Anemia y logro de aprendizaje en estudiantes del cuarto de primaria de la I.E.I.P.S.M N° 601491 Madre Teresa de Calcuta, San Juan Bautista 2022 - Celi Hidalgo, Mirtila Iris (2023)
Study to determine the correlation between anemia and learning achievement in fourth grade students of the I.E.I.P.S.M. N° 601491 “Mother Teresa of Calcutta”, 2022. The study approach was quantitative, non-experimental, with a descriptive – correlational pattern and descriptive cross-sectional design. The population was 200 students and the sample was 132 participants from the 4th grade of primary sections A, B, C, D and E of the I.E.P.M No. 601491 “Mother Teresa of Calcutta”, San Juan Bautista, enrolled in 2022. The technique Document analysis - samples, was used in data collection and the instruments were the documentary record sheet and the report cards. The Statistical Package for Social Sciences (SPSS) programs, version 24 in Spanish and Excel spreadsheet, were used to process the data. Kendall's Tau-b test with a calculated value of 9.275 showed correlation between the variables, the Pearson correlation test with a value of rxy= 0.621 proved a high and positive relationship between the variables and the student's t test with p-value of 8.370 and significance of 5%, which allowed us to accept the hypothesis: there is a statistically significant relationship between anemia and learning achievement in 4th grade primary school students at the I.E.P.M. No. 601491 Mother Teresa of Calcutta, San Juan Bautista, 2022.